Implementasi Location Based Service Pendistribusian Bantuan Berbasis Android - Yulanda Yunus; Zufrianto Dunggio; Misrawati Aprilyana Puspa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The design of making an android-based aid distribution application aims to provide convenience in facilitating the village office in distributing aid by taking into account finding the distribution mileage so that the distribution process does not require large transportation costs, as well as distributing aid to the community in Nunukan Village, Bolaang Mongondow Utara Regency based on android by using location-based services. The design of this website uses the Research and Development method. This application is designed using PHP and HTML programming language software, namely Sublime Text, Java Programming Language Using Android Studio, and tools for modeling using UML (Unified Modeling Language).